Pembuktian Tindak Pidana Anak dalam Proses Peradilan Dilihat dari Pasal 1 Angka 27 Kitab Undang-Undang Hukum Acara Pidana (Kuhap) Studi Kasus pada Putusan 380/Pid.Sus/2022/Pnckr.”: Studi Kasus pada Putusan 380/Pid.Sus/2022/Pnckr.” - Abdul Hayy Nasution (Neolectura, 2022)
This research was conducted with the aim of knowing how the position of witnesses in criminal cases and what is the role of witnesses as one of the tools of evidence in criminal proceedings according to the Criminal Procedure Code. By using normative juridical research methods it can be concluded: that the position of a witness in a criminal case is a powerful means of proof to reveal and dismantle crimes. From the investigation stage to proof before the court, even in practice, the position of a witness is very important, often a determining factor and success in disclosing a case, because it can provide 'witness testimony' which is placed as the first of the five valid pieces of evidence as stipulated in the Article 184 KUHAP. Without the presence and role of a witness, it is certain that a case will become an obscure event, because in the legal system in force in Indonesia, what is the reference for law enforcers is a statement or statement that can only be obtained from a witness or expert, as well as the role of the witness' statement as wrong. One means of evidence in the criminal case process will be able to reveal the crime that occurred. Because the testimony of the witness is of its nature as the main means of evidence, it will be difficult for the witness' statement to prove that the crime charged against the defendant is denied by the defendant.